ANALYSIS AND MINIMIZATION OF THE RISKS OF HARMFUL DEPENDENCIES IN THE PROCESS OF CONTINUOUS INTEGRATION AND IMPLEMENTATION OF SOFTWARE CODE - Danil N. Alekseev; Renat M. Khamitov (International Journal of Advanced Studies)
Continuous integration and continuous deployment (CI/CD) processes have become essential elements of modern software development, enabling automation and optimization of work processes. However, these processes come with risks associated with vulnerabilities in the dependency chain, which can lead to serious consequences such as unauthorized access and data leakage. The article discusses the need to implement reliable mechanisms for detecting and mitigating dependency risks to improve the reliability of CI/CD.